Capillary-resident EphA7+ pericytes are multipotent cells with anti-ischemic effects through capillary formation. (30th August 2019) - Yoshida, Yuri; Kabara, Maki; Kano, Kohei; Horiuchi, Kiwamu; Hayasaka, Taiki; Tomita, Yui; Takehara, Naofumi; Minoshima, Akiho; Aonuma, Tatsuya; Maruyama, Keisuke; Nakagawa, Naoki; Azuma, Nobuyoshi; et al.
Abstract: The presence of pericytes (PCs) with multipotency and broad distribution along capillary suggests that microvasculature plays a role not only as a duct for blood fluid transport but also as a stem cell niche that contributes to tissue maintenance and regeneration. The lack of an appropriate marker for multipotent PCs still limits our understanding of their pathophysiological roles. We identified the novel marker EphA7 to detect multipotent PCs using microarray analysis of an immortalized PC library. PCs were isolated from microvessels of mouse subcutaneous adipose tissues, then EphA7 + PCs called capillary stem cells (CapSCs) were separated from EphA7 − control PCs (ctPCs) using fluorescence-activated cell sorting system. CapSCs had highly multipotency that enabled them to differentiate into mesenchymal and neuronal lineages compared with ctPCs. CapSCs also differentiated into endothelial cells and PCs to form capillary-like structures by themselves. Transplantation of CapSCs into ischemic tissues significantly improved blood flow recovery in hind limb ischemia mouse model due to vascular formation compared with that of ctPCs and adipose stromal cells. These data demonstrate that EphA7 identifies a subpopulation of multipotent PCs that have high angiogenesis and regenerative potency and are an attractive target for regenerative therapies. : Abstract : Role of capillary-derived EphA7+ pericytes in regenerative potency.